Comparação de ésteres de breu com resinas hidrocarbônicas na aplicação de adesivos hot melt base metaloceno - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The growth of the hotmelt adhesive market is driven by the increasing demand for solvent-free adhesives and their use in sectors such as packaging, sanitary products, and the automotive industry due to their sustainable nature. In recent years, the industry has focused on seeking new alternatives for raw materials that take into account economic factors, availability, and the sustainability of natural resources. Given the importance of studies related to hotmelt adhesives due to their wide range of applications and their significance for the industry, the present work aims to evaluate hotmelt adhesives produced with metallocene-based polyethylene as the base polymer, considering the growing research on their superior properties compared to other polymers, such as thermal stability and Fischer Tropsch wax. The study also investigates the variation of the tackifier, including hydrocarbon resin, glycerol ester, and hydrogenated glycerol ester, for application in cardboard packaging. In summary, hydrogenated rosin esters have proven to be good alternatives to replace C5 hydrocarbon resin as tackifiers in hotmelt adhesives. They exhibit good thermal stability, compatibility with the polymer, and satisfactory performance in bonding tests, with the hydrogenated glycerol ester intended for the food industry being the closest to C5 hydrocarbon resin. However, C5 hydrocarbon resin is still widely used due to better compatibility and a more attractive color for customers.
Keywords: Compatibilidade; Embalagem; Recursos renováveis; Metaloceno; Breu; Compatibility; Packaging; Renewable resources; Metallocene; Rosin; CNPQ::ENGENHARIAS